Parent‐Metabolite Pharmacokinetic Modeling and Pharmacodynamics of Veliparib (ABT‐888), a PARP Inhibitor, in Patients With BRCA 1/2–Mutated Cancer or PARP‐Sensitive Tumor Types. (7th April 2017) - Niu, Jing; Scheuerell, Christie; Mehrotra, Shailly; Karan, Sharon; Puhalla, Shannon; Kiesel, Brian F.; Ji, Jiuping; Chu, Edward; Gopalakrishnan, Mathangi; Ivaturi, Vijay; Gobburu, Jogarao; Beumer, Jan H.
Abstract: Veliparib (ABT‐888) is a novel oral poly‐ADP‐ribose polymerase (PARP) inhibitor that is being developed for the treatment of hematologic malignancies and solid tumors. Although the pharmacokinetics of veliparib have been studied in combination with cytotoxic agents, limited information exists regarding the pharmacokinetics (PK) of chronically dosed single‐agent veliparib in patients with either BRCA 1/2 –mutated cancer or PARP‐sensitive tumors. The objectives of the current analysis were to characterize the population pharmacokinetics of veliparib and its primary, active metabolite, M8, and to evaluate the relationship between veliparib and M8 concentrations and poly‐ADP‐ribose (PAR) level observed in peripheral blood mononuclear cells (PBMCs). Seventy‐one subjects contributed with veliparib plasma concentrations, M8 plasma concentrations, and PAR levels in PBMCs. Veliparib and M8 concentrations were modeled simultaneously using a population PK approach. A 2‐compartment model with delayed first‐order absorption and the elimination parameterized as renal (CLR /F) and nonrenal clearance (CLNR /F) adequately described veliparib pharmacokinetics. The pharmacokinetics of the M8 metabolite was described with a 2‐compartment model. Creatinine clearance(CLCR ) and lean body mass (LBM) were identified as significant predictors of veliparib CLR /F and central volume of distribution, respectively. For a typical subject (LBM, 48 kg; CLCR, 95 mL/min), total clearance (CLR /F + CLNR /F), and central and peripheral volume of distribution for veliparib were estimated as 17.3 L/h, 98.7 L, and 48.3 L, respectively. At least 50% inhibition of PAR levels in PBMCs was observed at dose levels ranging from 50 to 500 mg.